Posted by **Andrew** on Wednesday, November 24, 2010 at 7:32pm.

Use the Gauss-Jordan method to solve the equation:

3x-5y-2z=-9

-4x+3y+z=11

8x-5y+4z=6

## Answer This Question

## Related Questions

- Algebra - Use the Gauss-Jordan method to invert 1 0 0 2 -1 0 0 0 1 A1= 1 1 1 A2...
- Pre-Calculus - Solve for x,y,z, & w using the Gauss-Jordan Elimination Method 5x...
- math - solve by the gauss-jordan method x+y+z=6 3x+2y-z=4 3x+2y+2z=11
- MATH - solve the system of linear equations using the Gauss- Jordan elimination ...
- Algebra - How would you solve this matrices using the Gauss-jordan elimination ...
- Alg 2 - Math - need help with hw... Use Gauss-Jordan to solve 3x – 2y + z = 6 3x...
- math - What is the difference between Gauss Jordan method and the Echelon method
- Algebra - Using the Gauss-Jordan method need to determine the coefficients a,b,c...
- Algebra - Use Gauss-Jordan to solve 3x + 2y = -4 4x – 2y = -10
- Algebra - Use Gauss-Jordan to solve 3x + 2y = -4 4x – 2y = -10

More Related Questions